Effect of renalase (RNLS) gene polymorphisms (rs1088700 and rs2576178) on plasma RNLS level in hemodialyzed patients affected by arterial hypertension and coronary artery disease - Steć, Anna (Polish Journal of Public Health, 2018)
Introduction. We have previously reported that rs10887800 and rs2576178 renalase (RNLS) single nucleotide polymorphisms (SNPs) are associated with the susceptibility to arterial hypertension (HY) and coronary artery disease (CAD) in hemodialyzed patients (HD). However, the underlying mechanism of this link remains undefined.Aim. In the present study we examine the influence of above-mentioned RNLS gene variants on plasma renalase level in subgroups of HD patients affected by HY and CAD.Material and methods. In total, 309 hemodialyzed patients participated in the study (157 males and 152 females, mean age 64.1±14.10 years). Rs10887800 and rs2576178 RNLS gene polymorphisms were genotyped using PCR-RFLP method. Plasma RNLS level was assessed by ELISA (USCN Life Science Inc., Wuhan, China). The data were analyzed using SPSS Statistics 23.Results. Regarding rs10887800 polymorphism, hypertensive AA homozygotes had significantly lower plasma RNLS level (28.93±9.94 µg/mL) compared to AG (34.06±12.79 µg/mL) and GG carriers (36.54±12.01 µg/mL), p=0.002. Among CAD patients no differences in plasma RNLS concentrations between rs10887800AA, AG and GG carriers were observed (31.52±10.95 µg/mL, 34.75±13.37 µg/mL, 34.44±13.10 µg/mL, respectively), p=0.615. For the rs2576178 variant, both HY and CAD participants did not differ in terms of plasma RNLS levels with regard to the particular genotypes, p>0.050.Conclusion. Obtained results extend our previous findings and indicate for the first time that rs10887800 RNLS gene variant modifies the level of plasma RNLS in hemodialyzed patients with HY but not in those with CAD. The study provides, thus, a new insight into the potential mechanisms through which RNLS gene variants modulate the risk of cardiovascular diseases among patients with end-stage kidney disease.